A Study on Role of Financial Institutions in Reducing Intensity of Poverty in Maharashtra: Examining the Impact of Financial Institutions on Poverty Reduction in Maharashtra (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The Maharashtra Employment guarantee scheme was intended to provide productive employment to the rural population and there by solve the problem of rural poverty. The scheme has since been reviewed and revised several times. The NREGS thus, assumes special significance in terms of reaching out to the poor, hitherto bypassed by the processes of economic growth, facing multiple deprivation – socio-political, economic and spatial. A central argument in the paper is that awareness generation and empowerment of the poor are the two most critical pre-conditions for effectively operationalising rights-based programmes such as the MEGS and NREGS.